The Influence of Bus Rapid Transit System on Urban Development: An Inquiry to Boston and Seoul BRT Systems’ Performance Indicators - Lutfi Prayogi (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
This article explores the relation between bus rapid transit (BRT) system and urban development. This article was written through a multi-staged comprehensive literature review. It includes a general overview on widely observed BRT performance indicators. Findings in terms of the influence of Boston Silver Line 4 and 5 and Seoul BRT systems on urban development around the systems are quoted and used as case studies. Investigation on the performance of Boston SL 4/5 and Seoul BRT systems are provided. This article shows that two BRT systems of different performance are able to influence urban development around the systems in varying degrees. Further investigation is needed to explain the nature of the relation between BRT performance and influence towards urban development.